The Role of Transformative Research in Forensic Medicine: Advancing the Understanding of Cause, Manner, and Time Since Death - Bhoopendra Singh (Indian Journal of Forensic Medicine and Pathology, 2025)
Forensic medicine plays a critical role in medico-legal investigations, particularly in determining the cause, manner, and time since death (TSD). In recent years, transformative research driven by interdisciplinary innovation and technological advancements has signi𿿿cantly enhanced forensic capabilities. Molecular autopsy, post-mortem imaging, and genomic pro𿿿ling are revolutionizingcause-of-death analysis, while digital forensics, injury biomechanics, and AI-based assessments are improving accuracy in identifying the manner of death. Meanwhile, emerging tools such as microbial forensics, RNA degradation studies, and then atomicrobiomics offer new potential for precise TSD estimation. Despite these advancements, implementation in India faces challenges due to infrastructural, educational, and policy constraints. This editorial emphasizes the need for ethical integration of transformative research into practice and urges investment in forensic research infrastructure and training to meet the evolving demands of justice delivery in India and beyond.